2007
DOI: 10.1021/om061001o
|View full text |Cite
|
Sign up to set email alerts
|

New Enantiomerically Pure Alkylimido Molybdenum-Based Alkylidene Complexes. Synthesis, Characterization, and Activity as Chiral Olefin Metathesis Catalysts

Abstract: Molybdenum olefin metathesis catalysts that contain aliphatic 1-phenylcyclohexylimido (NPhCy) and 2-phenyl-2-adamantylimido (NPhAd) groups and (S)-Biphen or (R)-Trip)(THF) ligands (Biphen = 3,3′-di-tert-butyl-5,5′,6,6′-tetramethyl-1,1′-biphenyl-2,2′-diolate; Trip = 3,3′-bis(2,4,6-triisopropylphenyl)-2,2′-binaphtholate) have been prepared. Their catalytic activity and enantioselectivity in desymmetrization reactions such as ring-closing metathesis of amines and lactams and ring-opening/cross-metathesis of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To prevent polymerization of norbornenes in ring-opening cross metathesis (ROCM) reactions, norbornenes with substituents in the 7-position are generally required, at least for the reported Mo and W catalysts . In certain cases, ROCM of substituted norbornenes with an excess of the cross-partner employing Ru-based metathesis catalysts has been observed, as has ROCM of silyl-substituted norbornenes with ethylene .…”
Section: Resultsmentioning
confidence: 99%
“…To prevent polymerization of norbornenes in ring-opening cross metathesis (ROCM) reactions, norbornenes with substituents in the 7-position are generally required, at least for the reported Mo and W catalysts . In certain cases, ROCM of substituted norbornenes with an excess of the cross-partner employing Ru-based metathesis catalysts has been observed, as has ROCM of silyl-substituted norbornenes with ethylene .…”
Section: Resultsmentioning
confidence: 99%
“…In the above polymerization systems (olefin insertion and metathesis polymerization), both imido and anionic donor ligands should play essential key roles in stabilizing the catalytically active species and/or controlling the electronic/steric environment during the catalytic reactions, which should strongly affect the catalytic activity as well as monomer reactivity. Molybdenum-alkyidenes that contain an adamantylimido ligand often show unique characteristics in olefin metathesis, ,, especially in the polymerization of acetylene as well as ring-closing metathesis, and the metal−imido group has been shown to promote high-oxidation-state coordination and organometallic chemistry as a spectator or supporting ligand through modification of the N substituent . Thus, we are interested in admantylimido chemistry, because the ligand should be better able to access as a σ donor than the arylimido analogues, which would stabilize the catalytically active species and lead to higher activity in olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes, which are easily accessed from the reaction of a Mo bistriflate with an appropriate lithium pyrrolide, are converted to the desired diolates (e.g., complexes in Scheme 5) upon exposure to chiral biphenols or binaphthols; the resulting diolates can be used without isolation or purification to promote enantioselective olefin metathesis reactions with efficiencies and selectivities similar to those observed with purified catalysts 40. The above investigations indicated that pyrrole molecules generated via protonation by the chiral diols do not cause diminution of catalyst activity or reaction selectivity.…”
Section: Resultsmentioning
confidence: 99%